On the thermodynamics and its connection to structure in the Pt-Pd-Cu-Ni-P bulk metallic glass forming system. (November 2021) - Neuber, Nico; Gross, Oliver; Frey, Maximiliam; Bochtler, Benedikt; Kuball, Alexander; Hechler, Simon; Gallino, Isabella; Busch, Ralf
Abstract: Contrary to basic hard sphere structure models, recent studies revealed, significant structural differences between Pt-Cu-Ni-P and Pd-Cu-Ni-P metallic glass-forming liquids with the same stoichiometry. To cover the compositional space between both systems, platinum is subsequently replaced by palladium in the composition (Pt/Pd)42.5 Cu27 Ni9.5 P21 . For this systematic set of alloys, the thermodynamic properties, such as isobaric heat capacity, enthalpy and Gibbs free energy are assessed. A systematic drop of the Gibbs free energy difference between crystal and liquid, providing a lower estimate of the driving force for crystallization was observed, underlining the high glass-forming ability of the Pd-rich systems. Contrary to kinetic fragility data, a change of the thermodynamic fragility can be observed, drawing the picture of an increasing thermodynamically strong behavior with rising Pd-content. Further, the temperature induced changes of the total structure factors S(Q) were monitored using high-energy synchrotron X-ray diffraction. Focus was laid on the changes on the medium-range length scale, by analyzing changes of the first sharp diffraction peak. Here a good correlation of the changes in peak-width and the thermodynamic fragility was found. From the determination of the excess enthalpy, large amounts of residual enthalpy in the glassy state were observed for the Pt-rich alloys, supporting the increased ductility of these alloys. The current findings further carve out the different roles of the topologically similar Pt and Pd in the Pt/Pd-Cu-Ni-P alloy system and how the change of the structural motifs on the medium range order is influencing thermal properties such as enthalpy and heat capacity. Graphical abstract: Image, graphical abstract